2017
DOI: 10.1016/j.amepre.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Smoking-Cessation Assistance: Before and After Stage 1 Meaningful Use Implementation

Abstract: Introduction Brief smoking-cessation interventions in primary care settings are effective, but delivery of these services remains low. The Centers for Medicare and Medicaid Services’ Meaningful Use (MU) of Electronic Health Record (EHR) Incentive Program could increase rates of smoking assessment and cessation assistance among vulnerable populations. This study examined if smoking status assessment, cessation assistance, and odds of being a current smoker changed after Stage 1 MU implementation. Methods EHR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…In a similar setting of urban health centers, Silfen et al found that 19.2% received counselling, 5.5% received medication only, and 7.8% received both. The findings of the prevalence of documentation of counselling and ordering of tobacco cessation medications in this sample are similar to other studies …”
Section: Discussionsupporting
confidence: 91%
“…In a similar setting of urban health centers, Silfen et al found that 19.2% received counselling, 5.5% received medication only, and 7.8% received both. The findings of the prevalence of documentation of counselling and ordering of tobacco cessation medications in this sample are similar to other studies …”
Section: Discussionsupporting
confidence: 91%
“…Rates of tobacco use screening are high in NY and nationally, largely because of Meaningful Use Stage 1 that included this measure, but cessation counseling remains low. 42,43 Combining screening and counseling therefore masks poor performance on the treatment measure. Second, less than half of sites were adhering to the smoking-cessation counseling guideline during the baseline period, which meant there was room for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first to examine rates of smoking documentation in EMRs from a multistate sample of CHCs before and after the 2011 changes. In an earlier study of 26 CHCs in Oregon, Bailey et al also found an increase in smoking assessment comparing 2014 to 2010 (adjusted OR 2.52 [95% CI 2.37, 2.69]) although in these CHCs the smoking status documentation rate was high even in 2010 (93.9 percent) …”
Section: Discussionmentioning
confidence: 94%